(3GdCQLhRI GdSjfGFjI aj GdWHs - (3GdMSjf Hf YHO Gddg Hf GdMSf Hf Ydj Hf SjfG , CHh Ydj GdnHrdNqj Ke GdoHNGQqj GdeYQha HGHf SjfG, (B427 (3g`s
(3ChdgG (B:s
(3bGd GdTjN GdQFjS GdeGgQ GdYdGeI GdMeO ddg GdYdi GdbGOQ Pi GdWhd hGdMhd GdYRjR GdbGgQ GdWH MaX UMI HQA GdeQV ef SHH ai HOf efP YQV s
(3BNQgG (B:s
(3hbO aQZJ ef LejY GdYde hGdBf CbWY HbhI eced JeJ GdCQLhRI HEYGfI Gddg s
(3GdfSNI HgG MhGTs
(3HgG fXGe GdJYbjHIs
(3cJHJ HYV GdcdeGJ HGdMeQIs
(3YdjgG Jedc HGSe dWai GdeJWHH HjeGQSJGf fhQ GdOjf GdTgjO SfI (B1075(3g` s
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B2 - (3U (B241s
Keywords: (3GdWHs